Options for Digital Birth Certificates - Dharwadker, Sanjay; Mills, Samuel (World Bank, Washington, DC, 2019)
Birth certificates are the cornerstone for establishing legal identity around the world. Despite their importance, birth certificates are frequently simple, handwritten paper documents or computerized printouts, submitted with little attention to security. The birth certificate issuance process is often decentralized, potentially leading to different formats within the same country. These features make birth certificates relatively easy to forge and difficult to authenticate. In many countries, applying for a passport requires the submission of a birth certificate, a process that can be inefficient, and at the same time may not enable the full authentication of individuals. A similar situation may exist in other circumstances, for instance, when applying for school or university admission, driver’s licenses, marriage and separation certificates, and welfare benefits; enrolling for health care or health insurance; or registering to vote. One way to solve this problem is to make the birth certificate a highly secure document (like a banknote or passport), with personalization and issuance completed under highly secure conditions. Some countries are using a digital birth certificate (DBC). The birth certificate as a digital credential has become relevant in the context of sustainable development goal. Given the increasing digitization of state records and processes, as well as greater connectivity among departments, a DBC, if issued in a secure manner, can enable more timely processing and a greater level of authentication. In addition to having the capacity and administrative processes in place to manage DBCs, countries require a corresponding legal framework to recognize DBCs. This guidance note provides select country examples of manual and electronic birth registration and certification processes and discusses the principal requirements for moving toward DBCs, with suggestions on how to meet the requirements.